Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan Pengguna Wifi Indihome Kota Tasikamalaya - Wildan Army Abdillah; Madya Pranata, Rengga; Iqbal Nurfauzan, Muhammad (Jurnal Manajemen dan Bisnis Kreatif, 2024)
This study aims to determine the influence of product quality and service quality on customer satisfaction, with a focus on IndiHome services. The method used in this research is a quantitative method, where questionnaires are used as the data collection instrument. The research sample was taken from a portion of IndiHome customers who have used the service. The data analysis results indicate that product quality and service quality have a positive and significant impact on customer satisfaction. This is supported by a determination coefficient of 70.3%, indicating that 70.3% of the variability in customer satisfaction can be explained by product quality and service quality. The implications of this research are that the company must continue to pay attention to and improve the quality of their products and services to maintain and enhance customer satisfaction. This study provides a deeper understanding of the factors that affect customer satisfaction in the telecommunications service industry. Furthermore, these findings can be used as a basis for developing more effective and competitive marketing strategies. By understanding the importance of product quality and service in increasing customer satisfaction, companies can direct their efforts to ensure that the products offered meet high-quality standards and that the services provided meet customer expectations. These steps will not only help retain existing customers but also attract new ones, thereby increasing the company's competitiveness in the telecommunications service market.